History of Friedrich II of Prussia $1 (BVolume 07s - Carlyle, Thomas, 1795-1881 (Salt Lake City, UT : Project Gutenberg, 2008)
"History of Friedrich II of Prussia $1 (BVolume 07" by Thomas Carlyle is part of a six-volume biography published between 1858 and 1865. This monumental work chronicles the life of Frederick the Great, examining him as author, soldier, king, and man. Carlyle spent thirteen years researching and writing this history, touring German battlefields and amassing extensive source materials. The result captivated readers with its vivid characterizations, wit, and narrative power, earning praise from luminaries who called it a supreme work of literary genius. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/History_of_Friedrich_II._of_Prussia,_Called_Frederick_the_Great
Release date is 2008-06-16
Produced by D.R. Thompson and David Widger
Keywords: Social problems; Frederick II, King of Prussia, 1712-1786; Prussia (Germany) -- History -- Frederick II, 1740-1786